PENGARUH ORIENTASI KEWIRAUSAHAAN DAN KEUNGGULAN BERSAING TERHADAP KINERJA PEMASARAN USAHA KULINER DI KECAMATAN SANGATTA UTARA - Cantika, Alifia Putri; Ellyawati, Noor; Sutrisno, Sutrisno (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
There are already many culinary businesses in North Sangatta District, which causes competition to maintain the market. Culinary business actors need to understand the importance of maintaining the market, namely by developing strategies and paying attention to marketing performance. The research objective is to determine the effect of entrepreneurial orientation and competitive advantage on the marketing performance of culinary businesses in the North Sangatta District. The population in this study amounted to 3,909 culinary businesses in Sangatta Utara District. The research sample amounted to 98 respondents, determined using the Slovin formula. Data collection techniques include distributing questionnaires. This type of research uses descriptive methods with a quantitative approach. The analysis method used in this research is multiple linear regression analysis with the help of the SPSS version 27 analysis tool. Based on the results of the simultaneous test, entrepreneurial orientation and competitive advantage simultaneously affect marketing performance. The conclusion from the results of this study is that entrepreneurial orientation and competitive advantage can improve the marketing performance of culinary businesses in North Sangatta District. Keywords: Competitive Advantage, Entrepreneurship Orientation, Marketing Performance